Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4314/tjpr.v18i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-nociceptive, anti-inflammatory and hepatoprotective effects of methanol extract of Mazus pumilus (Burm. f.) Steenis (Mazaceae) herb

Abstract: Purpose: This study was designed to investigate the anti-nociceptive, anti-inflammatory and hepatoprotective activities of the methanol extract of Mazus pumilus (Mazaceae) herb. Methods: Anti-nociceptive activity was determined using hot plate, tail flick and acetic acid-induced writing methods. Carrageenan-induced rat paw edema (0.1 mL of 1 %) model was used for the assessment of anti-inflammatory activity. The methanol extract was administered orally at three different doses (150, 300 and 600 mg/kg) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This taxon also possesses antibacterial and antifungal properties (Safdar et al, 2017). Ishtiaq et al (2019) demonstrated the anti-nociceptive, anti-inflammatory and hepatoprotective effects of the methanol extract of M. pumilus. Additionally, this species has wide medicinal uses in the local and popular tradition.…”
Section: Distribution Mazus Pumilus Is Native Of Easternmentioning
confidence: 94%
“…This taxon also possesses antibacterial and antifungal properties (Safdar et al, 2017). Ishtiaq et al (2019) demonstrated the anti-nociceptive, anti-inflammatory and hepatoprotective effects of the methanol extract of M. pumilus. Additionally, this species has wide medicinal uses in the local and popular tradition.…”
Section: Distribution Mazus Pumilus Is Native Of Easternmentioning
confidence: 94%